Situational Analysis of Leptospirosis in Sik, Kedah, Malaysia: 2014 - 2017 - S.S., Rakesh; H., Ismail; M. H., Ja’afar; Emilin, Noorul; Rahmah, Siti (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Leptospirosis is endemic in Malaysia. Over the past decade, there have been an increased in the number of leptospirosis cases and outbreaks. Previous leptospirosis studies examined the incidence rate, disease burden and risk factors for leptospirosis in Malaysia, but not at district or state level. Very little is known about the leptospirosis situation at district or state level. Therefore, we conducted a study to find out about leptospirosis situation in Sik district. MATERIALS AND METHODS: We conducted a cross-sectional study from January 2014 till December 2017 in Sik District, Kedah. Information on cases admitted to Sik hospital was obtained from the health office of Sik district. Socio-demographic data and laboratory results were obtained from the patient’s hospital records. We performed a descriptive analysis, followed by univariate and multivariate analysis. RESULT: From January 2014 until December 2017, 286 suspected cases of leptospirosis were admitted to Sik Hospital. Of the 286 cases, 150 were confirmed cases of leptospirosis and 136 probable cases. In our study, teenager (11-20 years of age) and older adults (aged 51-60 years) were more prone to infection with leptospirosis. Fever, vomiting, anorexia, cough, and myalgia were common symptoms. Laboratory findings in 108 confirmed leptospirosis cases showed a high white blood cell count of more than 10 X 109/L in half of the patients (50.0%), a serum aspartate aminotransferase (AST) of more than 50 U/L in 41 cases (38.0%), a platelets count of less than 150 X 109/L in 39 cases (36.1%), a serum creatinine kinase more than 308 U/L in 39 cases (36.1%) and serum alanine aminotransferase (ALT) less than 50 U/L in 33 cases (30.6%). Multivariate analysis showed leptospirosis infection was associated with cough (p=0.02. 95% CI=0.28-0.91) and abdominal pain (p=0.03, 95%CI =1.07-4.93). In our study, a higher number of leptospirosis cases were due to household infection compared to recreational activities. CONCLUSION: Teenagers and the elderly were more prone to leptospirosis infection, and the trend of household infection is increasing compared to recreational activities. Therefore, by knowing the current situation, the causes and the source of infection will help in the development of better control and prevention measures for leptospirosis.